Prevalence of Increased Alpha Angles as a Measure of Cam-Type Femoroacetabular Impingement in Youth Ice Hockey Players. (June 2013) - Philippon, Marc J.; Ho, Charles P.; Briggs, Karen K.; Stull, Justin; LaPrade, Robert F.
Background: It has been reported that relative to other sports participants, ice hockey players suffer from cam-type femoroacetabular impingement (FAI) in higher numbers. α angles have been reported to increase with the likelihood of symptomatic FAI. It is unclear how prevalent increased α angles, commonly associated with cam FAI, are in asymptomatic young ice hockey players. Hypothesis: There would be a higher prevalence of α angles associated with cam FAI in youth ice hockey players than in a non–hockey-playing (skier) youth control group. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 61 asymptomatic youth ice hockey players (aged 10-18 years) and 27 youth skiers (controls) (aged 10-18 years) underwent a clinical hip examination consisting of the flexion/abduction/external rotation (FABER) distance test, impingement testing, and measurement of hip internal rotation. The hip α angle was measured by magnetic resonance imaging, and labral tears and articular cartilage lesions were documented. Hockey players were grouped according to their USA Hockey classification as peewees (ages 10-12 years), bantams (ages 13-15 years), and midgets (ages 16-19 years). Results: Overall, ice hockey players had significantly higher α angles than did the control group, and hockey players had a significant correlation between increased age and increased α angles, while the control group did not. In the ice hockey group, 75% had an α angle of ≥55°, while in the skier group, 42% had an α angle of ≥55° ( P < .006). Hockey players were 4.5 times more likely to have an α angle commonly associated with cam impingement than skiers. Midget players had the highest risk of increased α angles. Conclusion: Even at young ages, ice hockey players have a greater prevalence of α angles associated with cam FAI than do skier-matched controls. Properties inherent to ice hockey likely enhance the development of a bony overgrowth on the femoral neck, leading to cam FAI.